Study of lipid profile in cases of non-diabetic stroke - Kar, Ayaskanta; Dash, Chinmayananda; Murmu, Malati; Mahesh K. P., Karun (International Journal of Advances in Medicine, 2018)
Background: To study serum lipid profile in non-diabetic patients with stroke and to determine whether there is any significant correlation between them and to compare the serum lipid profile between ischaemic and haemorrhagic group. Design: Case control study. Methods: The current study was done in the Department of Medicine VIMSAR, Burla, Odisha. Total 100 patients of completed stroke (Ischaemic63 and haemorrhagic37) and 30 controls were included in the study. All cases were adult (more than 14 years of age). Patients with suspected embolic stroke, diabetes (Type 1 and 2) and patients on lipid lowering drugs were excluded from the study. Routine investigations and fasting serum lipid profile was done. Results: 45 patients had elevated serum total cholesterol levels out of which 75.56% had Ischaemic stroke and 24.49% had haemorrhagic stroke. 24 cases had elevated serum Triglyceride levels of which 66.67% had Ischaemic stroke and 29.17% had haemorrhagic stroke. 76.47% of cases having elevated serum LDL cholesterol suffered from Ischaemic stroke where as 20.59% had haemorrhagic stroke. Conclusions: A statistically positive correlation was found between serum total cholesterol, Triglyceride, LDL levels and the risk of stroke.